STRATEGI KOMUNIKASI HUMAS DALAM MEMBANGUN CITRA PERGURUAN TINGGI STUDI KASUS di UNIVERSITAS WIJAYAKUSUMA PURWOKERTO - Astrid Devitasari (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2025)
Universitas Wijayakusuma Purwokerto (UNWIKU) has experienced a decline in the number of new student admissions over the past five years, amidst increasing competition from public and private universities. This study examines the public relations communication strategies employed by UNWIKU in building and maintaining a positive institutional image. Using a qualitative-descriptive approach and a single case study design, data were collected through participant observation, in-depth interviews with public relations leaders, management staff, students, alumni, and community members, as well as documentation of public relations activities. Data analysis followed the Miles & Huberman model: data reduction, data display, and conclusion drawing. The findings reveal four strategic pillars: targeted communication segmentation, utilization of print, electronic, and digital media, implementation of community service and CSR programs, and alumni empowerment as image ambassadors. While these strategies have effectively enhanced awareness and engagement, challenges such as limited human resources and digital infrastructure remain to be addressed. Recommendations include strengthening public relations capacity, establishing a regular evaluation system, and optimizing digital platforms.